2014
DOI: 10.1103/physrevlett.112.183902
|View full text |Cite
|
Sign up to set email alerts
|

Relative Refractory Period in an Excitable Semiconductor Laser

Abstract: We report on experimental evidence of neuronlike excitable behavior in a micropillar laser with saturable absorber. We show that under a single pulsed perturbation the system exhibits subnanosecond response pulses and analyze the role of the laser bias pumping. Under a double pulsed excitation we study the absolute and relative refractory periods, similarly to what can be found in neural excitability, and interpret the results in terms of a dynamical inhibition mediated by the carrier dynamics. These measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
125
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(130 citation statements)
references
References 24 publications
5
125
0
Order By: Relevance
“…They display the typical behavior already reported in Ref. [14], i.e., a sharp jump at the excitable threshold and an increase of the excitable threshold for lower pump values. The excitable threshold increase is accompanied with a reduction of the height of the response step, until no more jump is visible as the excitable regime disappears at the benefit of a gain switching regime.…”
Section: Spike Latencysupporting
confidence: 83%
See 2 more Smart Citations
“…They display the typical behavior already reported in Ref. [14], i.e., a sharp jump at the excitable threshold and an increase of the excitable threshold for lower pump values. The excitable threshold increase is accompanied with a reduction of the height of the response step, until no more jump is visible as the excitable regime disappears at the benefit of a gain switching regime.…”
Section: Spike Latencysupporting
confidence: 83%
“…The active zone consists of two InGaAs quantum wells for the gain section and one InGaAs quantum well for the SA section. A 4-μm diameter micropillar is then etched and the micropillar is further coated with a thick SiN layer to prevent oxidization and to improve heat dissipation [14]. The micropillar is pumped cw by a fiber-coupled array of laser diodes and focused onto the sample with a microscope objective.…”
Section: Spike Latencymentioning
confidence: 99%
See 1 more Smart Citation
“…However, only the response to a single perturbation has been analyzed and, contrary to many other optical excitable systems where the refractory time has been directly or indirectly observed [19][20][21][22][23], the refractory period of this excitable system has not been measured yet.…”
Section: Introductionmentioning
confidence: 99%
“…The system is highly simplistic, only adding an additional quantum well in order to achieve excitability. In 2014, Selmi et al [46] demonstrated that a similar system experiences a refractory period. Upon initial excitation by an optical pulse, the system remains nonexcitable during its refractory period.…”
Section: Excitable Photonic Devices For Rcmentioning
confidence: 99%